Hungarian Monitoring, 2 July 1990 . [Magyar rádiófigyelő], 1990. július 2 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - CPSU congress - Latest Le Pen attack - Italian politicians lead the Common Market Domestic Affairs: - Debate over the introduction of the local government law - Explosive materials left behind by Soviet troops - Electing constitutional judges - Eppelmann-Für agreement on military cooperation - Debates over vacated barracks - Exit from the Warsaw Pact - State Audit Office examines the Gabčíkovo-Nagymaros case Economy: - Dismissals of enterprise leaders - Researching alternative sources of energy in Hungary - Miners' strike Külpolitika: - SZKP-kongresszus - Újabb Le Pen támadás - Olasz politikusok a Közös Piac élén Belpolitika: - Vita az önkormányzati törvény bevezetéséről - Szovjet csapatok által hátrahagyott robbanóanyagok - Alkotmánybírók megválasztása - Eppelmann-Für megegyezés a katonai együttműködésről - Viták a kiürített laktanyák körül - Kilépés a VSZ-ből - A Bős-Nagymaros ügyet vizsgálja az ÁSZ Gazdaság: - Vállalati vezetők leváltása - Alternatív energiaforrások kutatása Magyarországon - Bányászok sztrájkja